Nursing Care for Sensory Perception Disorder in Auditory Hallucinations with Occupational Therapy: Case Study - Silfia, Annisa; Suryawantie, Tanti (CV. Literasi Publikasi Indonesia, 2025)
This paper aims to analyze mental health nursing care in patients experiencing sensory perception disorder, specifically auditory hallucinations, who receive occupational therapy through drawing at the Camar Room of the West Java Provincial Mental Hospital. The research method employed is a descriptive approach with a case study involving one patient, supported by Evidence-Based Practice (EBP). The findings suggest that occupational therapy through drawing is effective in reducing the symptoms of auditory hallucinations in schizophrenia patients. This therapy can be considered as a non-pharmacological alternative for managing auditory hallucinations in patients with sensory perception disorders